Extrapyramidal reactions with metoclopramide. Issue 6500 (5th October 1985) - Bateman, D N; Rawlins, M D; Simpson, J M
Abstract : The epidemiology of extrapyramidal reactions to metoclopramide was studied by examining reports in the Adverse Reactions Register of the Committee on the Safety of Medicines and comparing these with prescribing figures by general practitioners in the United Kingdom for metoclopramide (Maxolon). In the period 1967-82 there were an estimated 15.9 million prescriptions and 479 reports of extrapyramidal reactions (455 of dystonia-dyskinesia, 20 of parkinsonism, and four of tardive dyskinesia). When corrected for prescribing rates the relative risk of dystonia and dyskinesia was 1.8 in female compared with male patients (95% confidence interval 1.4-2.2). The overall reporting rate for dystonia and dyskinesia was 28.6/million prescriptions but was significantly more common in young adults (p less than 0.0001) and especially girls and women aged 12-19 (190.7 reports/million prescriptions). By contrast parkinsonian reactions were significantly more common in the elderly (p less than 0.0001).